POTENSI WISATA BAHARI PULAU-PULAU KECIL DI KAWASAN KAPOPOSANG KABUPATEN PANGKEP - Krishna Samudra; Mulyono S. Baskoro; Sugeng H. Wisudo; Budhi H. Iskandar (Bogor Agricultural University, 2010)
Kapoposang area is located in Pangkep Regency consist of six small islands and consist of high marine and fisheries resources, especially the white sandy beaches and coral reefs within its ecosystem. This is an important factor for further development of marine tourism based on conser-vation. Identification of marine tourism resources is the first step in development planning process. Focus Group Discussion (FGD) and survei method was applied in this research. The result show that this area is a potential area to be developed as marine tourism area based on conservation consideration.